Analysis and experiment of stress concentration in penetration fuze buffer materials under stress wave incursion - Zhang, An; Liu, Peng; Zhang, He (Frontiers in Physics, 2024)
To enhance the impact resistance of penetration fuze, this paper investigates the response of fuze buffer materials to stress waves and develops a model for stress wave transmission inside the fuze. The stress concentration impacts of different cell structures of Imitation Bamboo Type Penetration Fuze Buffer Protection Structure (IBS) under stress wave action are compared and analyzed. The paper elucidates the impact of different cell parameters on stress concentration impacts, establishes nonlinear fitting functions of Stress Concentration Factor (SCF) and cell parameters, and solves the prediction error. Based on the wave function expansion method, an expression for Dynamic Stress Concentration Factor (DSCF) when stress waves interact with the potting material is derived, and numerical results of DSCF around bubbles under different physical parameters are provided. Finally, dynamic impact tests are conducted on the combined buffer scheme of penetration fuze. Simulation results indicate that, during various stages of penetration, the stress concentration level of traditional structures is greater than that of IBS. For the same penetration overload, the peak stress is inversely proportional to the wall thickness, with the side length having minimal impact on the peak stress, and the peak stress being directly proportional to the curvature. DSCF around the bubbles is directly proportional to the dimensionless wave number, and DSCF does not vary significantly with changes in bubble radius. With an increase in bubble depth, DSCF correspondingly increases, and low-frequency stress wave impacts have a more significant impact on the bubble DSCF. Impact test results show that, under an initial velocity impact of 50m/s, the overload peak attenuation rate is 39.42%, and under an initial velocity impact of 70m/s, the overload peak attenuation rate is 32.87%. IBS can effectively protect the electronic components inside the fuze.